2010
DOI: 10.1007/s00106-010-2121-y
|View full text |Cite
|
Sign up to set email alerts
|

Lärm in Kindertagesstätten

Abstract: Children and teachers in nursery schools are subjected to high sound levels. Therefore, the education and early sensitization of children to noise in order to prevent prospective hearing damage, e.g. using the "noise light", should be set as a goal. Soundproofing measures are also possible. Further investigations to assess the effects of these measures are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…In daycare centers and schools, children's voices produce considerable levels of noise; the equivalent noise levels (Leq) measured over 8 hours were 80.1 dB (A) near the teachers' ears and 70.87 dB (A) in the classroom. The Lmax was 112.55 dB (A) near the teachers' ears and 103.77 dB (A) in the classroom 7 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In daycare centers and schools, children's voices produce considerable levels of noise; the equivalent noise levels (Leq) measured over 8 hours were 80.1 dB (A) near the teachers' ears and 70.87 dB (A) in the classroom. The Lmax was 112.55 dB (A) near the teachers' ears and 103.77 dB (A) in the classroom 7 .…”
Section: Discussionmentioning
confidence: 87%
“…Over an 8-hour period, the authors recorded average noise levels of 80.1 dB (A) near the teacher's ear and 70.87 dB (A) in the classroom. The maximum noise level near the teacher's ear was 112.55 dB (A) and that in the classroom was 103.77 dB (A) 7 .…”
Section: Introductionmentioning
confidence: 93%
“…Existing means to reduce the physical strain experienced as a result of work-related factors and improve the working posture in this occupation have yet to be evaluated and validated. In addition to the physical stress levels, various studies indicate that preschool teachers are also exposed to high psychological stress levels (Eysel-Gosepath et al 2010;Rudow 2004). As complaints regarding excessive stress in the preschool workplace are being increasingly reported (Darius et al 2013), this is a current and key topic that will only become exacerbated with time as the number of children entering preschool increases (Darius et al 2013;Grant, Habes, and Tepper 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Eysel-Gosepath et al reported that annoyance in preschool is dependent on several additional parameters. The stress level is, for example, less for older teachers and full-time employees, which indicates that there is a subjective rating [ 17 ]. The study of Sjodin et al pointed out that there is no significant correlation between the subjective noise annoyance and the objective noise measurement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that most average L eq8h are under the threshold of hearing impairment, teachers often complain of tinnitus or acute hearing loss [ 15 , 20 ]. The peak values of individual measurements in nursery schools were up to 113–117 dB (A)[ 17 ] and occurred particularly in free playing sections [ 17 , 21 ]. Peak values of more than 130 dB (A) may cause an acute acoustic trauma.…”
Section: Introductionmentioning
confidence: 99%